2013
DOI: 10.2147/ijn.s47413
|View full text |Cite
|
Sign up to set email alerts
|

Linear polyethylenimine produced by partial acid hydrolysis of poly(2-ethyl-2-oxazoline) for DNA and siRNA delivery in vitro

Abstract: Polyethylenimines (PEIs) are the most efficient synthetic vectors for gene delivery available to date. With its high charge density and strong proton-buffering effect, PEI has an ability to condense DNA and small interfering RNA at physiologic pH. However, the polymer suffers from the disadvantage of high cellular toxicity. To reduce its cellular toxicity, we synthesized linear PEIs by partial hydrolysis of poly(2-ethyl-2-oxazoline). Three linear PEIs with different hydrolysis percentages (30%, 70%, and 96%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The formation of polymer/DNA complexes is a necessary step in gene delivery, which needs to protect the gene cargo from enzymatic degradation [42]. The migration of shSmad3 gene was completely retarded when the weight ratio (N/P ratio) was 5 or higher (Figure 2(b)), indicated that PEG-Et 1:1/shSmad3 complexes could be prepared at those N/P ratios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of polymer/DNA complexes is a necessary step in gene delivery, which needs to protect the gene cargo from enzymatic degradation [42]. The migration of shSmad3 gene was completely retarded when the weight ratio (N/P ratio) was 5 or higher (Figure 2(b)), indicated that PEG-Et 1:1/shSmad3 complexes could be prepared at those N/P ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with PEI-Et and PEI 25 kDa, PEG-Et 1:1 exhibited significantly lower cytotoxicity in VSMCs (Figure 3(a)); as for the cytotoxicity of polymer/scrambled shRNA complexes (Figure 3(b)), PEG-Et 1:1/scrambled shRNA complexes also exhibited lower cytotoxicity than PEI-Et/scrambled shRNA and PEI 25 kDa/scrambled shRNA complexes. PEG modification could help reduce the number of PEI amino groups by coupling reaction to decrease the surface charge [42]. Therefore, lower cytotoxicity of PEG-Et 1:1 was probably attributed to the reduction of positive charge after PEG modification.…”
Section: Discussionmentioning
confidence: 99%